A Vietnam trilogy : veterans and post traumatic stress, 1968, 1989, 2000 - Scurfield, Raymond M. (Algora Pub., 2004)
Through the stories of veterans and the author's own understanding as a psychiatric social work officer in Vietnam and his extensive post-war experiences as a mental health professional, A Vietnam Trilogy describes the impact of war on veterans from a psy.